Towards unobtrusive patient‐centric access‐control for Health Information System. (27th May 2020) - de Carvalho Junior, Marcelo Antonio; Bandiera‐Paiva, Paulo
Summary: Patient consent is currently a missing piece on Health Information Systems (HIS) access permission. The control is needed to ensure personal data as the property of the individual, not data controllers or health‐care service providers. This is a newly‐designed access‐decision flow for HIS secured by Role‐Based Access Control (RBAC) including patient‐centric control. It makes use of Colored Petri‐Nets (CPN) to model RBAC restrictions. A Discretionary Access Control (DAC) functionality is added to Electronic Health‐Records (EHR) control to convey a patient's explicit authorization to their data in a non‐obstructive access flow. Mutual exclusion was designed to incorporate patient needs so that they could authorize healthcare professionals to access EHR data. Additional information was supplied to a PERMS Access Control matrix and this enabled DAC to be mimicked using existing RBAC Core functions. A minimal addition is proposed to incorporate RBAC‐aware systems with no significant drawbacks when compared with previous CPN simulations. The article also discusses the limitations of this technique and the favorable conditions for implementing new features.